Estimation and Management of Credit Concentration Risk - Valvonis, Vytautas (Ekonomika, 2007)
One of the most important risks for banks is the credit risk. Credit risk related problems arise for many reasons: too much concentrated credit portfolio, not adequate risk assessment of borrowers or inappropriate on-going monitor of exposures. etc. One of the main credit risk related problems is too concentrated credit portfolio. Credit concentration risk is defined as possibility for a bank to incur loss relatively (compared to bank’s capital, assets or total risk if it possible to estimate the latter) large loss from credit portfolio, so that this loss would endanger normal activity of a bank. Credit concentration risk may arise because of single large credit or several interrelated credits (e.g. borrowers from the same economic sector, geographic region, etc.). It is very important for a bank to identify possible sources of credit concentration, in order to be able to evaluate and manage this risk. Credit concentration risk can arise from many sources: large credit to single borrower; connected borrowers; borrowers having low quality ratings; borrowers from the same foreign countries or geographic region, economic sector, etc.; the same type of collateral; the same type of credits; credits in the same currency and other sources. The list of credit concentration sources is not complete or finite, because it is not possible to list all the credit concentration sources. It is up to the bank to decide whether particular credit concentration source is material and should be controlled. Having identified the most important credit concentration sources for the bank, one needs to measure how large is the concentration risk. Two types of measurement units are used for measuring concentration risk: nominal measurement units, like exposure value or units related to amount at risk, like economic capital. One of the most important credit concentration risk management tools is credit risk limits. Limits can be classified by different attributes: risk limiting or informative limits; nominal limits or related to amount at risk; absolute or relative limits; ex ante or ex post limits. The article discusses how limits are to be set and applied, what is the role of bank supervisors in managing credit concentration risk. Credit concentration risk can be managed not only by system of limits, but also using other tools: • Monitoring of credit concentration sources and information of bank top management; Mitigation of credit concentration risk and usage of credit derivatives; Sale of credits; Securitization; Application of credit portfolio models, including risk based pricing; Changing of credit portfolio or credit segments; Stress testing. The largest international banks use most the above listed tools to manage credit risk, including credit concentration risk. Usage of one or the other tools depends on bank’s business specifics, its credit portfolio and many other internal and external factors. For smaller banks availability of credit risk management tools is limited. Smaller banks use only several tools, most often monitoring of credit concentration sources and information of bank top management and stress testing. The latter two tools are also the only to available tools for Lithuanian banks, thus they are discussed in greater detail in the article. The concluding part of the article discussed proposals for Lithuanian banks, how to manage concentration risk: the role of parent undertakings, possibilities to use credit risk limits, monitoring of credit concentration sources, information of top management, stress testing issues are discussed.